2019
DOI: 10.1007/978-3-030-15526-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Leadership Across Countries: The Role of Informal Institutions

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…For example, the literature has started to explore the relationship between social capital and leadership (e.g. Anderson & Sun, 2015;Chen 10 et al, 2016;Felix et al, 2020). Despite a sizeable quantity of the leadership literature focusing on the relationships between leaders and followers, empirical research has revealed that leaders usually spend considerable amounts of time with others both inside and outside of the organization (Eva et al, 2019).…”
Section: Social Capitalmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the literature has started to explore the relationship between social capital and leadership (e.g. Anderson & Sun, 2015;Chen 10 et al, 2016;Felix et al, 2020). Despite a sizeable quantity of the leadership literature focusing on the relationships between leaders and followers, empirical research has revealed that leaders usually spend considerable amounts of time with others both inside and outside of the organization (Eva et al, 2019).…”
Section: Social Capitalmentioning
confidence: 99%
“…The economic situation and context are also relevant when defining leadership (Antonakis et al, 2003;Felix et al, 2020). To capture individual wealth, we used two dummy variables representing whether the individual has purchased a house (property ownership equal to one and zero otherwise) and has either gained employment or opened a business during the last 12 months (job status equal to one and zero otherwise).…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Raposo et al (2008) set forth an historical view of an entrepreneur as being an individual who takes risks correlated with uncertainty, who can provide financial capital, a person of innovation and creativity, a decision maker; a leader of an industry; a manager, director or a supervisor; economic resources organizer and coordinator; a business owner; a referee; a contractor; and a locator of resources between alternative uses (Abuhashesh, 2019a). According to Kirkley (2016), those perceived to be entrepreneurial can be assigned the following attributes: independent, creative, ambitious, goal driven, risk taker, achiever, and networker (Felix et al, 2020). Studying the behaviors of entrepreneurs is a fundamental way to clarify which ones lend support to an enterprise and help it to thrive.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in entrepreneurial economies have already led to detailed studies, such as those of McClelland (1972) [24]. Over the years, the dynamics themselves have developed differently from country to country, as noted by Felix, Aparicio, and Urbano (2020) [37], who mention several indicators.…”
Section: Comparative Entrepreneurship and An Analysis Of Ebcs In Higher-education Students From Brazil And Portugalmentioning
confidence: 99%